Glocalization of Character Education Based on Keris Culture: Traditional Ecological Studies in Elementary Schools - Ike Yuli Mestika Dewi; Nadi Suprapto; Neni Mariyana; Heru Subrata; Mohamad Suhaidi (Universitas Pendidikan Ganesha, 2025)
The implementation of character education in primary schools often lacks contextual relevance, relying on normative frameworks that do not connect learning to students’ cultural identity. This study aims to analyze the effectiveness of integrating keris culture and traditional ecological knowledge into character education through a glocal pedagogical approach. This quantitative survey involved 70 primary school students as the sample. Data were collected using a 20-item Likert-scale questionnaire and analyzed descriptively based on percentages. The results indicate high levels of agreement among students on indicators such as respect for culture (77.1%), environmental awareness (71.4%), and curiosity about traditions (74.3%), demonstrating strong internalization of character values through culturally embedded learning experiences. The findings confirm that integrating cultural heritage and traditional ecological knowledge can enhance character value internalization, particularly in respect for culture, environmental awareness, and curiosity about traditions. Furthermore, the glocal approach enables universal values such as honesty, responsibility, and collaboration to acquire deeper meaning when linked to local cultural experiences. The implications suggest that culture-based character education is not only effective in shaping students’ ethics and cultural identity but also relevant in promoting social and ecological sustainability in a global era.